Evaluation of the Effect of Nanosilver and Bismuth oxide on the Radiopacity of a Novel Hydraulic Calcium Silicate-based Endodontic Sealer: An In vitro Study - Teena Sheethal Dsouza; Aditya Shetty; Kelvin Peter Pais; Meenakumari Chikkanna; Fahad Hamoud Almutairi; Yazeed Abdulaziz Alharbi; J. Suresh Babu; C. Swarnalatha; Abhishek Singh Nayyar (Journal of Medical Physics)
Background and Aim: A wide range of dental materials have incorporated the concept of nanotechnology into their composition to enhance their physical and antimicrobial properties. In this pretext, silver nanoparticles (AgNPs) are among the most commonly used nanoparticles which are exceptionally noteworthy for their role in medical applications as an antibacterial agent. Another essential, desirable physical characteristic of all endodontic cements is their radiopacity, while in similar context, various radiopacifying agents such as bismuth oxide, barium sulfate, and even AgNPs have been incorporated in endodontic sealers to enhance their physical properties. The aim of the present study was to assess whether the incorporation of AgNPs and 10% bismuth oxide imparted the required radiopacity to the novel cement material (Nano CS) as per the requirement and standards laid by the International Organization for Standardization (ISO) guidelines and whether it complied with the ISO 6876:2001 specifications to achieve the necessary norms. Materials and Methods: The structural characteristics of the novel cement material (Nano CS) were observed using energy-dispersive X-ray analysis under a Zeiss Gemini 500 Field Emission Scanning Electron Microscope, while radiopacity of the test material (Nano CS) was assessed with the help of an aluminum (Al) step‐wedge using a nondestructive testing method following ISO guidelines. The optical density of the test material (Nano CS) was tested with the specimens of mineral trioxide aggregate (MTA) as the standard cement material along with the specimens of enamel and dentin that were 1 mm thick, and Al of appropriate thickness with the desired and equivalent radiopacity. Results: The findings of the present study suggested MTA to have higher radiopacity index equivalent to 4.56 ± 0.00 mm thickness of Al when compared to the test material (Nano CS) (2.78 ± 0.01 mm thickness of Al) and enamel (4.09 ± 0.01 mm thickness of Al) and dentin (2.01 ± 0.01 mm thickness of Al) specimens. Furthermore, the radiopacity index of test material (Nano CS) was found to be more when compared to dentin, though, less when compared to the enamel specimens with the results being statistically highly significant (P < 0.001). Conclusion: The addition of nanosilver and bismuth oxide to the test material (Nano CS) imparted characteristic radiopacity, though the required specifications laid down by the ISO standards were not achieved. Increasing the concentration of the additives used might be considered to bring in the required radiopacity without having a significant impact on the physical and biological properties of the test material (Nano CS) intended to be used for endodontic applications.